CISCO CCNA Lab Guide - Neil Anderson
The IOS operating system; cisco device functions; the life of a packet; the cisco troubleshooting methodology; cisco router ans switch basics; cisco device management; routing fundamentals; dynamic routing protocols; connectivity troubleshooting; RIP configuration; EIGRP configutation;...Spanning tree troubleshooting; etherchannel configuration;...